Analysis of Educational Philosophy on Research and Technology Development at Pesantren: George R. Knight's Perspective - Ahmad Syauqi Fuady; Miftakhur Rizki; Eka Saptaning Pratiwi (Universitas Muhammadiyah Mataram, 2026)
The development of research-based science and technology presents challenges for pesantren in integrating religious and scientific knowledge in a coherent manner. Such integration requires not only curricular adaptation but alse a clear educational philosophy as a foundation for guiding educational practice. This study aims to: (1) examine the construction of educational philosophy, including its metaphysical, epistemological, and axiological dimensions in the integrative development of science-technology research; and (2) analyze the educational goals and institutional governance that support this development at MBS Al-Amin Bojonegoro. This qualitative case study employed document analysis and semi-structured interviews with key institutional actors. Peer debriefing was conducted to strengthen the credibility and validity of the data. Data were analyzed through five stages: data collection, coding, categorization, interpretation, synthesis and reporting using George R. Knight framework as an analytical lens.. The findings show that the development of science and technology research is grounded in two main paradigms, namely Nushusisasi Sains (Scripturalization of Science) and Saintifikasi Nushush (Scientification of Scripture). These paradigms position knowledge as originating from Allah Swt. and emphasize its ethical orientation toward human well-being. The integration of religion and science-technology is further reflected in its institutional governance, including curriculum structure, teacher development, and research-based learning process. This study contributes by providing a structured philosophical analysis of science -religion integration using George R. Knight’s framework and by showing how philosophical assumptions shape educational governance and research development in pesantren.